2014
DOI: 10.5617/jmi.v1i1.723
|View full text |Cite
|
Sign up to set email alerts
|

User Empowerment and Audience Commodification in a Commercial Television Context

Abstract: This paper aims to provide insights into the concept of 'user empowerment' in current -digital and connected-media industries. We start by defining empowerment as a concept rooted in certain research traditions that focus on user behaviour and capabilities in dealing with digital and connected technologies and the production, aggregation, distribution and consumption of content. We then oppose 'user empowerment' to 'audience commodification', a concept that highlights how the audience and its members are explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
8
0
4
Order By: Relevance
“…We will see a similar concern raised in the last article in this section -namely Gunnar Nygren's findings that journalists' increasingly reliance on social media may lead to an increasing homogenization of journalism, even while in other ways digital media more broadly may entail greater autonomy and creativity for journalists. These findings and tensions can be helpfully compared with what emerged as a prominent "red thread" in our Inaugural Issue -namely, just the question as to how far new media technologies and innovations may foster and/or frustrate autonomy (Bruns 2014;Jennes, Pierson and Van den Broeck 2014;Nyre 2014).…”
mentioning
confidence: 96%
“…We will see a similar concern raised in the last article in this section -namely Gunnar Nygren's findings that journalists' increasingly reliance on social media may lead to an increasing homogenization of journalism, even while in other ways digital media more broadly may entail greater autonomy and creativity for journalists. These findings and tensions can be helpfully compared with what emerged as a prominent "red thread" in our Inaugural Issue -namely, just the question as to how far new media technologies and innovations may foster and/or frustrate autonomy (Bruns 2014;Jennes, Pierson and Van den Broeck 2014;Nyre 2014).…”
mentioning
confidence: 96%
“…Additional studies analyze how users can gain more control or power (empowerment) over their media experiences [29], the different ways of watching TV [26,63], and how behaviors change according to audience profiles [4,16,56]. Finally, [67] considers the introduction of content recording technologies as a natural evolution that substantially changes the way people watch TV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is well established that technology plays a crucial role in the TV usage and value generation in the broadcasting market [70], thus, a great deal of attention has been given to the development and introduction of new technologies [14,45], to changes in audience behavior [7,29], and to impacts on market and business models [38,41]. Studies have been conducted on how content recording impacts different countries [33,38], however, even though some studies reported an increased usage of Catch-up TV, there has been little research on the international market and scientific community on how to organize and classify these new services.…”
Section: Introductionmentioning
confidence: 99%
“…Outros estudos importantes sobre as mudanças de comportamento analisam como os telespectadores podem ganhar mais controlo ou poder (empowerment) sobre suas experiências de média (Jennes et al, 2014), diferentes formas de assistir TV (Hess et al, 2012;Tsekleves, Whitham, Kondo, & Hill, 2011), como as tecnologias digitais afetam os padrões e rotinas das audiências e como os comportamentos mudam de acordo com diferentes perfis de audiência (Autor, 2013;Chaney et al, 2014;Saxbe, Graesch, & Alvik, 2011).…”
Section: Revisão Aprofundada Da Literaturaunclassified
“…Nos últimos anos, tem sido dada uma atenção significativa ao desenvolvimento e introdução de novas tecnologias na TV (Bury & Li, 2015;Netflix, 2015); a mudanças no comportamento da audiência (Beauvisage & Beuscart, 2012;Jennes, Pierson, & Van den Broeck, 2014;Vanattenhoven & Geerts, 2015); e aos impactos sobre os mercados e modelos de negócios (Kalia, 2014;Medina et al, 2015;Mohan, 2014). Têm, igualmente, sido realizados estudos sobre os impactos da gravação de conteúdos em diferentes países (Kalia, 2014;Medina et al, 2015).…”
unclassified